A product cost system for middle and small sized manufacturing firms and its implementation at TAKIMSAŞ as a case - Güreş, Doğan (My University, 1993)
unknown
Keywords: Endüstri mühendisliği; İmalat; KÜÇÜK İŞLETMELER-MALİYETLER; ORTA BOY İŞLETMELER-MALİYETLER